Dimensions and Outcome of Experience Quality in Outdoor Dining Casual : The Case of Outdoor Cafe in Indonesia - Karisma Sri Rahayu; Edy Yulianto; Andriani Kusumawati (Wacana Journal of Social and Humanity Studies, 2019)
This study to determine  the effect of experience  quality on customer  satisfaction  and customer  loyalty.  the relationship between  experience  quality  and customer  loyalty  indirectly  through  customer  satisfaction  is explained  in this study.  A total of 168 questionnaires were distributed  to respondents who already  had experience  visiting  and enjoying  food in natural outdoor  cafes in Malang,  Indonesia.  Data was collected  by direct survey to respondents and analyzed  using the Structural   Equation   Modeling   (SEM)   equation   and  then  analyzed   with  three   stages   of  inferential   statistics.   The demographics  of  the  respondents  were  also  described   in  this  study.  The  findings   of  this  study  indicate   that  the emergence of millennial  generations has made changes  in lifestyle  today. The results of hypothesis  testing of this study prove  that  experience  quality  has a positive  and significant  influence  on customer  satisfaction  and customer  loyalty. Customer  satisfaction  plays a partial mediating  role between experience  quality variables and customer  loyalty.